Case report: Epilepsy during the use of recombinant human growth hormone: a report on two cases and a literature review - Zhou, Yuan; Jia, Ruofan; Xu, Zhuangjian; Ma, Yaping (Frontiers in Pharmacology, 2024)
Background: Epilepsy during recombinant human growth hormone (rhGH) therapy is rare in children. The potential relationship between rhGH treatment and epilepsy remains unclear. Methods: We retrospectively analyzed the clinical data of two Chinese boys who experienced epilepsy during the use of rhGH and reviewed the relevant literature. Results: Case 1, an 8-year-2-month-old boy, was diagnosed with short stature, malnutrition, and congenital hypothyroidism. He kept taking levothyroxine sodium tablets for a long time. Recurrent febrile convulsions present at 6-7 years. Electroencephalogram and magnetic resonance imaging showed no abnormality, and no treatment was given. He was diagnosed with complex febrile convulsions. The boy started rhGH treatment (about 0.15 IU/kg/day, sc, qd) at 8 years and 4 months. The epilepsy occurred 3 times during 6 months of rhGH treatment. Electroencephalogram confirmed a definitive diagnosis of epilepsy. Then he discontinued rhGH treatment at 8 years and 11 months old and started taking levetiracetam (0.25 g, po, bid) for antiepileptic therapy. Epilepsy was well controlled four months later. He continued treatment with rhGH at 10 years and 3 months old till now, with no more epilepsy has recurred. He has been taking levetiracetam until now. Case 2, a 9-year-1-month-old boy, was diagnosed with central precocious puberty, predicted short final height and overweight. He started treatment with triptorelin (3.75 mg, im, q4w) and rhGH (about 0.15 IU/kg/day, sc, qd) at 9 years and 3 months old. He tended to fall repeatedly around 10 years old. Electroencephalogram showed a few medium-high amplitude 2 sharp waves and sporadic sharp slow waves in the left middle temporal region, sometimes involving the left posterior temporal region. He was diagnosed with epilepsy. After triptorelin discontinuance, the symptoms were not relieved and even worsened. Subsequently, he withdrew from rhGH, the symptoms occurred occasionally within a week and stopped after half a month. Electroencephalogram returned to normal. No further seizures during follow-up to date.During the use of rhGH in short stature children with complex febrile convulsions, or underlying lesions related to neurological impairment, or being treated with antiepileptic drugs, epilepsy may be induced.